PENEGAKAN HUKUM TERHADAP KEJAHATAN SEKSUAL MELALUI MEDIA SOSIAL MENURUT UNDANG UNDANG NOMOR 1 TAHUN 2024 TENTANG ITE - Salsabillah, Anggini; Kornelis, Yudi (SCIENTIA JOURNAL, 2025)
According to Law Number 1 of 2024 on Electronic Information and Transactions (ITE), this research focuses on law enforcement against sexual crimes occurring on social media. With the increasing use of digital platforms in society, sexual crimes on social media have become a growing concern. In this context, the ITE Law establishes a legal framework to address online sexual harassment violations, including the dissemination of obscene content, gender-based bullying, and sexual extortion. This study employs a normative juridical method to analyze legislation, documents, and case studies. The research reveals that although adequate legal mechanisms are in place, enforcing laws through social media against perpetrators of sexual crimes still faces several challenges. These challenges include low legal awareness, resource shortages, and difficulties in identifying perpetrators. To enhance law enforcement, further collaboration between the government, law enforcement agencies, and social media platforms is required, as well as improved digital literacy among the public. Consequently, it is expected that law enforcement against sexual crimes involving social media can provide better protection for victims